Homework Help

If (x)^1/3 + (y)^1/3 + (z)^1/3= 3xyz, then (a)x^3+y^3+z^3=0     (b)x+y+z=27xyz...

user profile pic

falsefantasy | TA , Grade 9 | (Level 1) Salutatorian

Posted January 10, 2013 at 7:50 AM via web

dislike 1 like

If (x)^1/3 + (y)^1/3 + (z)^1/3= 3xyz, then

(a)x^3+y^3+z^3=0     (b)x+y+z=27xyz

(c)(x+y+z)^3=27xyz    (d)x^3+y^3+z^3=27xyz

Which option is correct? Please explain with steps.

1 Answer | Add Yours

Top Answer

user profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted January 10, 2013 at 3:04 PM (Answer #1)

dislike 1 like

You need to raise to cube both sides, such that:

`(x^(1/3) + y^(1/3) + z^(1/3))^3 = (3xyz)^3`

`(x^(1/3) + y^(1/3) + z^(1/3))^2*(x^(1/3) + y^(1/3) + z^(1/3)) = 27(xyz)^3`

`(x^(2/3) + y^(2/3) + z^(2/3) + 2(xy)^(1/3) + 2(xz)^(1/3) + 2(yz)^(1/3))(x^(1/3) + y^(1/3) + z^(1/3)) = 27(xyz)^3`

`x + y + z + x^(2/3)y^(1/3) + x^(2/3)z^(1/3) + x^(2/3)y^(1/3) + y^(2/3)z^(1/3) + x^(2/3)z^(1/3) + y^(2/3)z^(1/3) + 2x^(2/3)y^(1/3) + 2x^(1/3)y^(2/3) + 6(xyz)^(1/3) + 2y^(2/3)z^(1/3) + 2y^(1/3)z^(2/3) + 2x^(2/3)z^(1/3) + 2x^(1/3)z^(2/3) = 27(xyz)^3`

Notice that only the option `x^3+y^3+z^3=0` check the given condition `x^(1/3) + y^(1/3) + z^(1/3) = 3xyz` , if `x=y=z=0` , hence, you may select the answer `a) x^3+y^3+z^3=0` .

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes